2019
DOI: 10.1097/spv.0000000000000718
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Pelvic Floor Muscle Force and General Strength and Fitness in Postpartum Women

Abstract: Objective The aim of the study was to determine whether measures of muscular strength and fitness are associated with pelvic floor muscle (PFM) force 1-year postpartum in a population of primiparous women who delivered vaginally. Methods This cross-sectional analysis is an ancillary study to an ongoing prospective cohort study and includes 203 primiparous women. Procedures collected 1-year postpartum included maximal PFM force, grip strength, trunk flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
3
0
1
Order By: Relevance
“…We found that strength in whole-body exercises was not correlated to PFM strength, which indicates that strength adaptions from heavy weightlifting exercises, such as back squats and deadlifts, are not specific to the PFMs. Consistent with our results, Moss et al (30) found no associations between PFM strength and different measures of strength and fitness (e.g., hand grip strength) in postpartum women. Several studies have compared PFM strength in female athletes/exercisers and nonexercisers, but the results are conflicting across studies (9).…”
Section: Discussionsupporting
confidence: 92%
“…We found that strength in whole-body exercises was not correlated to PFM strength, which indicates that strength adaptions from heavy weightlifting exercises, such as back squats and deadlifts, are not specific to the PFMs. Consistent with our results, Moss et al (30) found no associations between PFM strength and different measures of strength and fitness (e.g., hand grip strength) in postpartum women. Several studies have compared PFM strength in female athletes/exercisers and nonexercisers, but the results are conflicting across studies (9).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we found that the number of vaginal deliveries, 14,15,26 and a family history of POP, 24,27 were independent risk factors for low PFM strength, and that MVCP decreased as the number of vaginal deliveries increased in both premenopausal parous women and postmenopausal women. Previous research has shown that taking part in physical work, which causes increased stress on the PFM, can also decrease PFM strength, 14 which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…First, our study had a larger sample size and covered a wider age range compared with previous studies, in which participants tended to be younger. Additionally, ethnic differences may also be a contributing factor, given that previous literature has indicated that ethnicity can impact PFM strength 23,24 . Lastly, differences in the vaginal manometry instruments used across studies may also introduce bias into the data and contribute to differences in findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there were no differences in PFM strength between 30 women with no clinical diagnosis of pelvic floor disorders who were Pilates practitioners and sedentary controls [41]. In a cross-sectional analysis of 203 primiparous women 1 year postpartum, there were no significant associations between PFM force and measures of strength and fitness, including grip strength, trunk flexor endurance duration, percent body fat, or self-reported physical activity [42]. Similarly, another cross-sectional study found no association between physical activity level, assessed by questionnaire, and vaginal resting pressure, PFM strength and endurance [43].…”
Section: Evidence Suggesting No Difference In Pfm Strengthmentioning
confidence: 90%